Educational Communication Transformation in the New-Media Era: A Data-Driven Study on Learning Engagement - Lam, Hon Sum Forest (Simen Owen Academic Proceedings Series, 2026)
The rapid expansion of new-media technologies has transformed educational communication from a one-way transmission model to a participatory, data-rich ecosystem. Platforms such as live-stream channels and social-media discussions now shape how learners construct meaning and interact with instructors and peers. Despite progress in technology-enhanced learning, existing studies remain fragmented. Educational-technology research focuses on tool efficiency, communication studies emphasize discourse without quantitative validation, and data-analytics work often reduces engagement to behavioural traces. An integrated understanding of how media affordances, communicative practices, and data patterns jointly influence learning engagement is still lacking. This study develops the Integrated Educational Communication and Engagement Framework (IECEF) and applies it to a comparative case of a hybrid undergraduate course. Using a mixed-methods design, quantitative log data, sentiment analysis, and Python-based analytics were combined with qualitative interviews and thematic coding to examine behavioural, cognitive, and emotional engagement. The new-media-integrated course achieved a 37 % increase in behavioural participation, higher correlation between engagement and quiz performance (r = 0.42 vs. 0.29), and an 18 % rise in positive sentiment. Learners reported greater visibility, collaboration, and agency. The findings validate the IECEF as a cross-disciplinary model bridging education, communication, and data science. They provide actionable insights for designing data-informed, socially connected, and human-centered learning environments in the new-media era.